OPTIMALISASI PROFIT PADA PRODUKSI TEMPE KEDELAI BESAR DAN KECIL MENGGUNAKAN PROGRAM LINIER DENGAN METODE SIMPLEKS - Palahudin, Palahudin; Rozwa Zakiyyah, Alfia Naura; Selviranih, Andara; Rahma, Deuis; Sahal Ma’hadi, Muhammad Albi; Azzahra, Zharifa Putri (LP2M Universitas Bina Bangsa, 2025)
Tempeh is a traditional Indonesian fermented food made from soybeans. Tempeh has been widely used in Indonesia for many years. This research aims to optimize profit in tempe production using linear program with simplex method approach. This research will identify production factors that affect profit and formulate a linear program model with decision variables, objective function, and constraint function to get the optimal solution. This research shows that to get the maximum profit of Rp. 5,000,000, it must produce large tempeh and small tempeh, then it must produce 50 times of production.